What if Brecht Met Darwish? Resonance and Subversion in Majdalanie and Mroué' Four Walls and a Roof - Bousselmi, Meriam (Peripeti, 2026)
This article analyses Lina Majdalanie and Rabih Mroué’s Four Walls and a Roof as a scenic essay on censorship, exile, and the politics of speech under conditions of contemporary catastrophe. Reading the performance through Brecht, Darwish, Zweig, and theories of resonance, it argues that the work turns historical reference into a resource for artistic survival and subversion. It also proposes shaghaf as a concept for grasping the aesthetic and ethical force of Majdalanie and Mroué’s stage practice.